Implementasi Kebijakan Pengembangan Daerah Wisata oleh Pemerintah Kabupaten Karo (Studi Deskriptif Terhadap Wisata Danau Lau Kawar) - Okdamaiyanti, Yiska; Angelia, Nina; Muda, Indra (Universitas Medan Area, 2025)
This study analyzes the implementation of the policy for the development of Lake Lau Kawar tourist attractions based on the Van Meter and Van Horn policy implementation theory. The focus of the research includes policy standards and objectives, resources, characteristics of implementing agents, communication between implementing agencies, environmental conditions, and implementing dispositions. This study uses a qualitative method with a descriptive approach. Data is collected through in-depth interviews, direct observations, and analysis of policy documents. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawn. The validity of the data is maintained through triangulation of sources and methods. The results of the study show that although the tourism development policy has been regulated in Regent Regulation No. 32 of 2019 concerning Tourism Villages, its implementation has not been optimal. Limited infrastructure, lack of tourism promotion, lack of coordination between stakeholders, and lack of human and financial resources are the main obstacles. To increase the effectiveness of implementation, a strategy is needed that includes improving infrastructure, optimizing the budget, and increasing community involvement in tourism management.